(untitled) (Journal of Basic and Applied Research in Biomedicine, 2021)
Antioxidants are added to fresh and processed meat to prevent lipid oxidation, retard development of off-flavors, and improve color stability. Synthetic antioxidants have been confirmed for their toxicological and carcinogenic effects. Thus, the food industry now chooses natural products over synthetic ones. This study was carried out to investigate the effect of Rosemary extract (R.E.) and vitamin E on the quality of fried fillets of Nile tilapia (Oreochromis niloticus) during chilling and frozen storage. Fillets of Nile tilapia were treated with (R.E.) 0.1%, 0.2%, 0.3% and Vitamin E 0.1% then stored for 5,10 and 15 days at 4±1°C and for three months at -18±2°C. Then chemical tests including Peroxide value (PV), Thio-barbituric acid (TBA), Tri-methylamine-nitrogen (TMA-N) and Total volatile base-nitrogen (TVB-N) were done to evaluate the preservative effect of (R.E.) and vitamin E during storage. The TBA and PV increased in all treatments due to lipid peroxidation. Results showed that TMA-N,TVB-N, value of (R.E.) and vitamin E treated samples were significantly lower than those of the control samples (P<0.05). Results of our investigation revealed that R.E. retarded oxidative changes in chilling and frozen fried fillets of Nile tilapia whereas R.E. 0.1%, 0.2% and vitamin E 0.1% were not as effective as R.E. 0.3% on oxidative stability. Best oxidation inhabitation results on chilling and frozen fried fillets of Nile tilapia was obtained when employing of R.E. The obtained results also showed that there was a significant (p<0.05) enhancement in sensory quality attributes of fried fillets of Nile tilapia; samples treated with R.E. and vitamin E. Conclusion, The tested R.E. had a high effectiveness as antioxidative and antimicrobial should be utilized for extending the shelf-life through retarded the spoilage and enhancing quality attributes of fried fillets of Nile tilapia during chilling and frozen storage.